(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
The medieval pottery assemblage was concentrated mainly on the High Street and comprised mostly Scottish White gritty ware. Two medieval roof tiles and a small quantity of early post-medieval sherds were also recovered.